Innovative Airport Designs’ Infrastructures to support an Integrated Sustainable Tourism Policy for Sustainable Development and Public Health Protection - Katsoni, Vicky; Koliopoulos, Tilemachos (Turystyka i Rozwój Regionalny, 2020)
In this paper are investigated actions for public health protection in airports’ tourism facilities and actions that promote innovation at Airports’ sustainable construction infrastructures to minimize associated pollution threats. An integrated framework is presented based on a comprehensive and analysis of the community airport tourism centers and sustainable design facilities in sustainable construction infrastructures in transportation related to waste management facilities and energy recovery from landfill emissions that are produced at nearby places at airports. Research in Sustainable Airport Designs and Infrastructures is necessary to solve common operating problems, to adapt appropriate useful information technologies, and to introduce innovations into the airport tourism industry. The study reveals sustainability dimensions that are lagging or require much greater attention, such as sustainable designs, environmental management, monitoring, safety and public health protection of tourists at airport facilities. In this study are presented useful solutions for sustainable airport designs that promote sustainability supporting an Integrated Sustainable Tourism Policy for Public Health Protection and Sustainable Development within associated infrastructures and airport facilities. Useful conclusions are made for the airport tourism industry, sustainable infrastructures, environmental technologies, renewable resources, sanitary facilities and associative infrastructures developing innovative near-term solutions to meet demands placed on it.